One step synthesis of water-dispersible CoFe2O4 magnetic nanoparticles using triethylenetetramine as solvent and stabilising ligand - Ngoc, Kieu T. B.; Luyen, Pham V.; Khang, Nguyen C.; Nam, Pham H.; Manh, Do H.; Vinh, Pham V.; Hung, Pham V.; Lu, Le T. (Vietnam Journal of Science and Technology, 2016)
Magnetic CoFe2O4 nanoparticles were synthesised by one step synthetic method through thermal decomposition of Co and Fe precursors in triethylenetetramine solvent at high temperature. The advantage of this method is the ability to make monodisperse nanoparticles with high water-dispersibility and stability. The particle size can be tuned in the range of 7-11.3 nm by varying synthetic conditions. The obtained particles with small DLS size (less than 21 nm) are ready to disperse and stable in aqueous solution for weeks without any surface modification.